2020
DOI: 10.12669/pjms.36.4.1755
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of Zamzam water on blood pressure and heart rate variability

Abstract: Objective: There is a lack of studies exploring the effects of Zamzam water on human physiology. The present study determined the effects of Zamzam water on blood pressure and heart rate variability (HRV). Methods: This comparative interventional study was conducted at the Department of Physiology, of our university in March 2018. A total number of 97 female subjects drank 500 ml of either Zamzam water or mineral water in one minute. Finometer Pro and PowerLab (ADInstrumentsR) with ECG electrodes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…These authors showed that the hypothesis testing using paired T-test revealed significant prior and afterward cured with Zamzam water (p <0.05). While the study that was conducted by (27) showed that drinking Zamzam water leads to a significant rise in systolic pressure, diastolic pressure, heart rates, and the average pressure in patient arteries during one cardiac cycle within a few times after consumption. Also, they reported that drinking Zamzam water leads to a substantial rise in parasympathetic activity but does not affect cardiac sympathetic activity.…”
Section: Zamzam Water Diabetes and Hypertensionmentioning
confidence: 99%
“…These authors showed that the hypothesis testing using paired T-test revealed significant prior and afterward cured with Zamzam water (p <0.05). While the study that was conducted by (27) showed that drinking Zamzam water leads to a significant rise in systolic pressure, diastolic pressure, heart rates, and the average pressure in patient arteries during one cardiac cycle within a few times after consumption. Also, they reported that drinking Zamzam water leads to a substantial rise in parasympathetic activity but does not affect cardiac sympathetic activity.…”
Section: Zamzam Water Diabetes and Hypertensionmentioning
confidence: 99%